Turnover or turnaway? Competing risks analysis of male and female IT professionals’ job mobility and relative pay gap - Joseph, Damien (2015)
This study draws on distributive justice, human capital, and stigmatization theories to hypothesize relationships between relative pay gap and patterns of job mobility. Our study also expands the criterion space of job mobility by contrasting different job destinations when information technology (IT) professionals make job moves. We examine three job moves: (a) turnover to another IT job in a different firm, (b) turnaway-within to a non-IT job, and (c) turnaway-between to a different firm and a non-IT job. We analyze work histories spanning 28 years for 359 IT professionals drawn from the National Longitudinal Survey of Youth. We report three major findings. First, as hypothesized, larger relative pay gaps significantly increase the likelihood of job mobility. Second, IT males and IT females have different job mobility patterns. IT males are more likely to turn over than turn away-between when faced with a relative pay gap. Further, and contrary to predictions from human capital theory, IT males are more likely to turn away-within than turn over. This surprising finding suggests that the ubiquitous use of IT in other business functions may have increased the value of IT skills for non-IT jobs and reduced the friction of moving from IT to other non-IT positions. Third, and consistent with stigmatization arguments, IT females are more likely to turn away from IT than to turn over when faced with a relative pay gap. In fact, to reduce relative pay gaps, IT females tend to take on lower-status jobs that pay less than their IT jobs. We conclude this study with important theoretical, practical, and policy implications.